Applications of Hybrid Photovoltaic Modules with Thermoelectric Cooling. (March 2017) - Enescu, Diana; Spertino, F.
Abstract: Among the energy sources with low efficiency, thermoelectric systems are used for hybrid systems with improved performance. This paper provides a review of recent literature concerning the integration of ThermoElectric Cooling (TEC) devices into PhotoVoltaic (PV) generators to constitute PV-TEC systems. The role of TEC is to reduce the temperature of the PV cells, to increase the efficiency of the system, its power capacity and lifetime. The paper also contains a formulation of thermoelectric module equations referring to cooling capacity, rate of heat rejected to the ambient and input power, together with the electrical model of the PV generator.